PRESEPSI SISWA DAN GURU TERHADAP PEMBELAJARAN DARING DI SMA YAPIS MANOKWARI KELAS XI - Rahmatia Rahmatia; Syahira Syahira; Ardian Eko Sajaril (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2020)
Online learning is used by all levels of education without exception, as a result of the Covid-19 pandemic. But the effectiveness of online learning is still unknown, because teachers are more focused on teaching than conducting studies on online learning. So this study aims to determine the effectiveness of online learning during the Covid-19 pandemic at Yapis Manokwari High School. The method in this research uses descriptive quantitative method, in which quantitative data is in the form of a percentage of the results of the questionnaire, and descriptive data is in the form of a description of the percentage of the results of the questionnaire. In addition, data collection techniques also use interview techniques to strengthen students' questionnaire answers. The interview was conducted with a class XI teacher at SMA Yapis Manokwari. The sample used was 30 students. The results showed that students understood the use of online platforms in online learning, but online learning was not effective due to several factors, including: (1) signal, (2) time constraints, (3) noise from students due to forgetting to turn off the microphone. In addition, the results of interviews with teachers also show that online learning is not effective because it does not meet teacher expectations or does not achieve learning objectives compared to face-to-face learning. Abstrak Pembelajaran online digunakan oleh semua jenjang pendidikan tanpa terkecuali, akibat dari pandemi covid-19. Tetapi keefektifan pembelajaran online masih belum diketahui, dikarenakan guru lebih fokus mengajar daripada melakukan telaah mengenai pembelajaran online. Sehingga penelitian ini bertujuan untuk mengetahui keefektifan pemebelajaran online di masa pandemi covid-19 di SMA Yapis Manokwari. Metode dalam penelitian ini menggunakan metode kuantitatif deskriptif, yang mana data kuantitatif berupa presentase hasil angket, dan data deskriptif berupa pendeskripsian presentase hasil angket, selain itu teknik pengambilan data juga menggunakan teknik wawancara untuk memperkuat jawaban angket siswa. Wawancara dilakukan kepada guru pengajar kelas XI SMA Yapis Manokwari. Sampel yang digunakan berjumlah 30 siswa. Hasil enelitian menunjukkan bahwa siswa memahami penggunaan platform daring dalam pembelajaran online, tetapi pembelajaran online tidak efektif dikarenakan beberapa faktor, diantaranya: (1) signal, (2) keterbatasan waktu, (3) suara bising dari siswa akibat lupa mematikan mikrofon. Selain itu, hasil wawancara kepada guru juga menunjukkan bahwa pembelajaran secara online tidak efektif karena tidak memenuhi harapan guru atau tidak mencapai tujuan pembelajaran dibanding pembelajaran secara tatap muka.